The Relationship Between Health Locus of Control and Medication Adherence in Hypertensive Patients - Setianingsih, Endah; Herman, Herman; Budiharto, Ichsan (ProNers, 2024)
Background: Hypertension is a chronic condition that poses significant health risks if not properly managed. Adherence to antihypertensive medication is essential for controlling blood pressure and preventing complications. Health locus of control, which reflects an individual"™s beliefs about the control of their health outcomes, is considered a critical factor influencing adherence.Objective: This study aimed to investigate the relationship between health locus of control and adherence to antihypertensive medication among patients with hypertension.Methods: A quantitative cross-sectional study was conducted on 126 hypertensive patients at a primary healthcare center in Pontianak. Participants were selected using purposive sampling. Data were collected through validated questionnaires: the Multidimensional Health Locus of Control (MHLC) for measuring health locus of control and the Morisky Medication Adherence Scale (MMAS-8) for assessing medication adherence. The relationship between health locus of control and adherence was analyzed using Spearman"™s rho correlation.Results: Most participants exhibited a moderate level of adherence to antihypertensive medication. The findings revealed a significant positive relationship between health locus of control and medication adherence. Patients with a stronger internal health locus of control showed better adherence to their medication regimens, emphasizing the influence of personal beliefs on health behaviors.Conclusion: Strengthening health locus of control, particularly internal control, may improve adherence to antihypertensive medication. Healthcare providers should incorporate strategies to enhance patients' sense of control over their health to optimize hypertension management and outcomes.